2020
DOI: 10.1155/2020/5715893
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency Aggravates Hepatic Oxidative Stress and Inflammation during Chronic Alcohol-Induced Liver Injury in Mice

Abstract: Vitamin D deficiency has been reported in alcoholics. This study is aimed at evaluating the effects of vitamin D deficiency on chronic alcohol-induced liver injury in mice. Mice were fed with modified Lieber-DeCarli liquid diets for 6 weeks to establish an animal model of chronic alcohol-induced liver injury. In the VDD+EtOH group, mice were fed with modified diets, in which vitamin D was depleted. Vitamin D deficiency aggravated alcohol-induced liver injury. Furthermore, vitamin D deficiency aggravated hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
(58 reference statements)
1
9
0
Order By: Relevance
“…Furthermore, alcohol-dependent individuals often exhibit low vitamin D levels as a direct result of how alcohol exerts its influence on vitamin D metabolism (malabsorption of vitamin D, decreased levels of the vitamin-D binding protein, reduced ability to hydroxylate vitamin D in the liver), altered biliary excretion, insufficient food intake, or reduced sun exposure. Studies conducted on animals have shown that chronic alcohol use may result in decreased serum concentrations of 1,25-dihydroxyvitamin D due to impaired renal synthesis and/or increased degradation of 1,25-dihydroxyvitamin D. Further research is needed to identify different mechanisms which contribute to low vitamin D levels associated with excessive alcohol use or intoxication [ 12 , 27 , 28 , 29 ]. Chun-Qiu Hu et al (2020) conducted a study on animals and found that vitamin D deficiency exacerbates cellular apoptosis in alcohol-induced liver damage (it leads to hepatic inflammation and oxidative stress—through regulation of oxidative and antioxidant enzymes) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, alcohol-dependent individuals often exhibit low vitamin D levels as a direct result of how alcohol exerts its influence on vitamin D metabolism (malabsorption of vitamin D, decreased levels of the vitamin-D binding protein, reduced ability to hydroxylate vitamin D in the liver), altered biliary excretion, insufficient food intake, or reduced sun exposure. Studies conducted on animals have shown that chronic alcohol use may result in decreased serum concentrations of 1,25-dihydroxyvitamin D due to impaired renal synthesis and/or increased degradation of 1,25-dihydroxyvitamin D. Further research is needed to identify different mechanisms which contribute to low vitamin D levels associated with excessive alcohol use or intoxication [ 12 , 27 , 28 , 29 ]. Chun-Qiu Hu et al (2020) conducted a study on animals and found that vitamin D deficiency exacerbates cellular apoptosis in alcohol-induced liver damage (it leads to hepatic inflammation and oxidative stress—through regulation of oxidative and antioxidant enzymes) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on animals have shown that chronic alcohol use may result in decreased serum concentrations of 1,25-dihydroxyvitamin D due to impaired renal synthesis and/or increased degradation of 1,25-dihydroxyvitamin D. Further research is needed to identify different mechanisms which contribute to low vitamin D levels associated with excessive alcohol use or intoxication [ 12 , 27 , 28 , 29 ]. Chun-Qiu Hu et al (2020) conducted a study on animals and found that vitamin D deficiency exacerbates cellular apoptosis in alcohol-induced liver damage (it leads to hepatic inflammation and oxidative stress—through regulation of oxidative and antioxidant enzymes) [ 29 ]. There are also studies showing that excessive alcohol use is associated with increased serum levels of 25 (OH) D [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the subject has not been investigated in experimental animals treated with chronic ethanol. Only, it has been recently reported that Vit D deficiency may aggravate hepatic oxidative stress and inflammation in EtOH-treated rats [57].…”
Section: Discussionmentioning
confidence: 99%
“…Di Luzio ( 1962) was the first to assume that ethanol could disrupt the oxidative balance of hepatic cells, either acting as prooxidants or reducing the antioxidant level eventually leading to necrosis or apoptosis (Hu et al, 2020). The process of apoptosis is critical in the development of liver disease.…”
Section: Discussionmentioning
confidence: 99%